Graduate Education Students’ Perceptions - Noureddine, Rasha A. (2021)
Globally, educational institutes of all levels face challenges in equitable education delivery due to the global Coronavirus (COVID-19) pandemic forcing institutions online. A particular entity in the establishment of quality and equitable education is ensuring that linguistic approaches to teaching and learning are optimized. It is well established that translanguaging pedagogy supersedes monolithic language pedagogies in terms of best approach within multilingual linguistic landscapes. Despite the prevalence of literature attesting to the benefits of translanguaging, and the shift in favor of translanguaging pedagogy in northern higher education institutes, educational institutes of varying levels remain hesitant to adopt it. This study aimed to identify graduate education students’ perceptions of translanguaging within a multilingual and online educational context. To attain a holistic understanding of graduate education students’ perceptions of translanguaging, a mixed-methods approach was utilized for data collection whereby observations, surveys and interviews were conducted. The results indicated that graduate education students perceive translanguaging as a natural and normative practice, acknowledge its beneficial role in education, and do not differentiate between online and on-site teaching and learning approaches. However, participants remain reluctant to incorporate it within their personal practice, and contradict their personal perceptions, as recorded during observations and interviews. These results suggest that graduate education students’ perceptions align with principles defined within the literature, however, a need for translanguaging research awareness is required at the level of both the student and the teacher in the context of the study, and a better understanding of the implications of mode of delivery and its subsumed barriers is also needed.